La (re)territorialisation (discrète) des croyances africaines chrétiennes dans la métropole du Caire - Julie Picard (Territoire en Mouvement)
Territorial and religious contemporary recompositions linked to christendom seem to be difficult to grasp in a migratory, mobile context and a predominantly arab-muslim environment. However, stimulated by sub-saharan and christian migrants or encouraged by local religious institutions, this recompositions are actual, multiple and complex. Adjustments of migrants’ ritual practices, in space and time, as adaptation of institutions’ process of territorialisation in egyptian context become relevant to illustrate upheavals and flexibility that christian world experience in his relations with individuals and territories. From the example of the metropolis of Cairo and taking into account a panel of various scales, from micro-local to transnational, this article, while challenging the idea of religion’s deterritorialization, attemps to demonstrate how the diversification of human mobility and the context of increasing religious competition have to be taken into account to analyze at best trends existing between religions and territories.